Influence of Pressing Temperatures on Physical–Mechanical Properties of Wood Particleboards Made with Urea-Formaldehyde Adhesive Containing Al2O3 and CuO Nanoparticles - Silva, Luana Cristal Lirya [UNESP]; Lima, Felipe Oliveira [UNESP]; De Araujo, Victor Almeida [UNESP]; Dos Santos, Herisson Ferreira; Lahr, Francisco Antonio Rocco; Christoforo, André Luis; Favarim, Higor Rogério [UNESP]; de Campos, Cristiane Inácio [UNESP] (MDPI, 2024)
Particleboards have gained attention in the global market. Understanding their physical–mechanical behavior in the current technological context is essential due to adhesive polymerization, which depends on variables such as pressing time and temperature. Today, the use of nanoparticles has become a plausible option for improving the properties of polymers used in wood-based composites. This study evaluates the influences of the addition of non-commercial 0.5% aluminum oxide (Al2O3) and aluminum oxide copper (CuO) nanoparticles using a greener route with a lower environmental impact obtaining a urea-formaldehyde (UF)-based polymeric adhesive to manufacture particle composites of Eucalyptus urophylla var. grandis wood. Regarding characterizations, the resin properties analyzed were viscosity, gel time, and pH, as well as panel properties, including density, moisture content, thickness swelling, modulus of elasticity, modulus of rupture, and thermal conductivity. The results were compared with scientific publications and standards. The addition of nanoparticles interfered with viscosity, and all treatments indicated a basic pH. It was not possible to determine the gel time after 10 min. Nanoparticles added to the polymers in the internal layer did not cause an improvement in the swelling properties in terms of thickness, with no significant statistical difference for density and moisture content. The increase from 150 °C to 180 °C may have caused an improvement in all physical–mechanical properties, indicating that the higher temperature positively influenced the polymerization of the formaldehyde-based adhesive. Therefore, the additions of both nanoparticles (0.5% in each condition) led to a limitation in the material influence with respect to physical–mechanical performance.
Keywords: density; mechanical property; nanomaterials; physical property; polymeric adhesive; pressing temperature; thermal property; wood-based panel